Pengembangan lembar kerja peserta didik (LKPD) berbasis project based learning (PjBL) dalam materi IPS - Anita Rahmawati; Erik Aditia Ismaya (COLLASE (Creative of Learning Students Elementary Education), 2023)
The problem with this investigation is that the education received in the classroom is based exclusively on textbooks taken from individual institutions. The aim of this research is to create project-based social studies learning student worksheets (LKPD) for grade 6 elementary school students. Gathering the right information will help you do this. There was one subject matter expert, one learning design expert, one learning media expert, and three students who took part in separate experiments as part of this research. This investigation is referred to as “developmental research,”(RnD), and uses the ADDIE (analysis, design, development, implementation, and evaluation) development approach. Quantitative and qualitative data were collected from respondents. Data collection was carried out using structured interviews, questionnaires and document recording. In the data analysis procedure, qualitative descriptive analysis methodology and quantitative descriptive analysis were used. The results of the review of the collected data resulted in the following conclusions: (a) The material expert believes that the project-based learning LKPD is very good with a score of 92.00%; and (b) Learning design experts think that the LKPD is very good with a score of 93,000%. Based on (c) learning media expert evaluation findings and (d) individual trial results, it can be seen that virtual project based learning LKPD turned out to be very good (93.00%) and (94.04%), respectively.